343 External validation of tumour-free distance as novel prognostic marker in early-stage cervical cancer undergoing primary surgery. (13th November 2020) - Bizzarri, N; Pedone Anchora, L; Zannoni, G; Carbone, MV; Bruno, M; Fedele, C; Gallotta, V; Chiantera, V; Ferrandina, G; Fanfani, F; Fagotti, A; Scambia, G
Abstract : Introduction: Tumor-free distance (TFD), defined as the minimum distance of uninvolved stroma between the tumor and peri-cervical stromal ring, was recently proposed as predictive marker of recurrence in patients with early-stage cervical cancer treated by primary surgery (particularly if ≤3.5 mm). The aims of the present study were to assess the prognostic value of TFD and to compare TFD with other known prognostic markers in early-stage cervical cancer. Methods: Patients with pathologic FIGO 2009 stage IA1-IIB cervical cancer, treated by primary radical surgical treatment between 01/2000 and 12/2018, were retrospectively included. Adjuvant treatment was administered according to the presence of previously established pathologic risk factors. TFD was measured histologically on the hysterectomy specimen. Results: 368 patients were included in the study. 115 (31.2%) patients had TFD≤3.5 mm and 253 (68.8%) had TFD>3.5 mm. TFD≤3.5 mm was associated with worse 5-year disease-free survival (DFS) and overall survival (OS), compared with TFD>3.5 mm (p=0.028 and p=0.041, respectively) (figure 1 ). DFS and OS differences were more evident in subgroups of patients who did not receive adjuvant treatment (DFS, p=0.001 and OS, p=0.001) and who underwent laparotomy approach (DFS, p=0.017 and OS, p=0.034). TFD≤3.5 mm represented the strongest predictor for lymph node metastasis and pathologic parametrial involvement at both univariate and multivariate analysis (table 1 ). Conclusions: TFD≤3.5 mm represents a poor prognostic factor significantly associated with lymph node metastasis and pathologic parametrial infiltration. The possibility to obtain this parameter by radiological imaging makes it the easiest measurable pre-operative marker to predict the presence of high-risk pathologic factors.